Pembangunan Sistem Pemesanan Paket Wisata berbasis Web (Studi Kasus : Go Tour and Travel Malang) - Mona Adelina; Adam Hendra Brata; Ratih Kartika Dewi (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Go Tour and Travel Malang is a travel and trip orgaziner that located in Jalan Perumahan Citra Mendut Kavling 14, Malang. Go Tour and Travel Malang is a part of tourism service business. Go Tour and Travel Malang have served their customer for 2 years. Tourist attractions that offered is the tour destinations where located in Malang and its environs. Go Tour and Travel Malang make an offer tour packages to their customers. Tour packages that their provide are an affordable price for a number group of people, date derparture, tour activities, accommodation, and transportation. Marketing and disseminating information strategy by distributing brochures at certain location points, information from people around and also through social media, Facebook. Updating brochure that contains of new informations become an obstacle by needing waste much time. The customers data collecting which still conventional makes Go Tour and Travel Malang difficult to evaluate their business. Customers have to come directly to the Go Tour and Travel Malang office, contacting by whatsapp message, or calling by phone to Go Tour and Travel Malang. The strategy of disseminating information, marketing, and ordering processes can be a problem for customers who are outside the city of Malang. The web-based booking tour packages system is developed to overcome the problems found in the Go Tour and Travel Malang. The development of the system uses the waterfall model with an Object-Oriented approach. The developed system has been examined by unit testing using white-box testing technique, and validation testing using black-box testing technique. The results of all tests are valid.